Pengaruh Literasi Keuangan, Inklusi Keuangan, Financial Technology terhadap Kinerja Keuangan (Studi Kasus pada UMKM Mitra dan Binaan Kantor Perwakilan Bank Indonesia Provinsi Bengkulu) - Nensi Yuniarti Zs; Shelly Rizky Belyani; Furqonti Ranidiah; Indri Dwi Via; Yogi Hadhiyanto (Universitas Batanghari, 2023)
This study aims to examine the Effect of Financial Literacy, Financial Inclusion, Financial Technology on the Financial Performance of MSMEs assisted by Bank Indonesia Representative Office of Bengkulu Province. The research sample is the owners and financial staff of MSMEs assisted by Bank Indonesia Representative Office of Bengkulu Province. This research uses quantitative methods. The data collection technique in this study used a questionnaire, which is a data collection technique that was carried out by giving questions and written statements to the respondents to answer. The data analysis technique used in this study is the Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, t test, f test, r test, Multiple Linear Regression, Coefficient of Determination Test using SPSS assistance. The results showed that there was an influence of financial literacy on financial performance with sig = 0.041 and ð‘¡â„Žð‘–ð‘¡ð‘¢ð‘›ð‘” 2,099> ð‘¡ð‘¡ð‘Ž ( sig = 0.0584 and ð‘¡â„Žð‘–ð‘¡ð‘¢ð‘›ð‘” 0.551 < ð‘¡ð‘¡ð‘Žð‘ð‘’ð‘™ 1.677 simultaneously there is an effect of financial literacy, financial inclusion, financial technology on financial performance with sig = 0.000 and fcount 25.093. The R Square value is 58.6% and the remaining 41.4% is influenced by other variables that are not examined. The conclusions of this study indicate that there are two variables that have a significant effect, namely financial literacy on financial performance and financial inclusion on financial performance. And there is one variable that has no significant effect, namely financial technology on financial performance.